1983
DOI: 10.1038/bjc.1983.136
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural and biochemical observations on the effect of 4-hydroxyanisole plus tyrosinase on normal human melanocytes and keratocytes in tissue culture

Abstract: Cultures of melanocytes and keratocytes were exposed to 15 micrograms ml-1 tyrosinase and 4-hydroxyanisole (4-OHA) 5 X 10(-4) M to 5 X 10(-2) M for 1 to 24 h. No damage was suffered by either cell below 5 X 10(-3) M 4-OHA for 6 h, but higher concentrations and longer exposures extensively damaged both cells. Exposure of cells washed free of culture medium to tyrosinase and 4-OHA 1 X 10(-3) M for 1 h resulted also in extensive damage. This indicates that an early-formed toxic product of the reaction between tyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…7). Since the toxic role of oxygen radicals persists for about 24 h (Table 2), it is evident that, subsequently, other mechanisms must be involved, such as the disappearance from the medium of essential growth factors, which may be destroyed, or inactivated, by quinones, semiquinones and oxygen radicals formed during the autoxidation of phenols, and/or the possible concomitant formation of toxic radical polymers (Breathnach et al, 1983;Naish, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…7). Since the toxic role of oxygen radicals persists for about 24 h (Table 2), it is evident that, subsequently, other mechanisms must be involved, such as the disappearance from the medium of essential growth factors, which may be destroyed, or inactivated, by quinones, semiquinones and oxygen radicals formed during the autoxidation of phenols, and/or the possible concomitant formation of toxic radical polymers (Breathnach et al, 1983;Naish, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…The most active melanocytotoxic agent, to date, is an analog of tyrosine, 4-hydroxyanisole . Studies in vitro demonstrated its cytotoxicity against mammalian melanocytes (Riley et al, 1975;Breathnach et al, 1983), including human melanoma cells (Bleehen, 1976;Kanclerz & Aubert, 1984;Meyskens, 1984). Dewey et al (1977) observed 'regression' of Harding-Passey melanoma in 46% of the animals treated with intratumoural application of 4-OHA.…”
mentioning
confidence: 99%